PRODUCTIVITY OF LAYING HENS AN INDUSTRIAL HERD DEPENDING ON DENSITY OF THE MAINTENANCE IN CAGES OF MULTILEVEL BATTERIES - M. Sakhatsky; Yu. Osadcha; Vitalii Kuchmistov (Тваринництво та технології харчових продуктів, 2020)
According to the current norms (DSTD-AIC-04.05.) the density of keeping chickens in cages should be 22–25 hens/m2 , which corresponds to their provision with an area in the range of 400–450 cm2 /hen. This level of housing density does not coincide with the slightly more comfortable (13–20 hens/m2, or 490–750 cm2 /hen) established in the United States and EU countries for chickens of modern egg crosses (Council DirecƟve 1999/74/EC). Therefore, it is important to study the egg producƟvity of chickens of industrial flocks in 6–15-Ɵer cages baƩeries at a density in accordance with domesƟc and European standards. In the condiƟons of the modern industrial poultry complex in a comparaƟve aspect two variants of the maintenance of laying hens in cages of 12-Ɵer baƩeries are invesƟgated. The first variant of keeping provided laying of laying hens in cages according to the European norms – 14 hens/m2 (726 cm2 /hen), and the second – 25 hens/m2 (402 cm2 /hen) that corresponded to domesƟc norms. It was found that the maintenance of laying hens of modern high-performance cross for 44 weeks (unƟl reaching 62 weeks of age) in cages of 12-Ɵer baƩeries in density in accordance with the requirements of domesƟc standards (22–25 hens/m2, or 400–450 cm2 /hen) provides 32265 edible eggs (2023 kg of egg mass) from 1 m2 of poultry area, which is 1.8 Ɵmes more than the density required by European standards (13–20 hens/m2 , or 490–750 cm2/hen). In addiƟon, 85.2 million eggs were obtained from hens kept in 12-Ɵered cage baƩeries of a poultry house with an area of 2640 m2 in terms of density in accordance with domesƟc norms that is 37.6 million eggs more than from their counterparts, retained by European standards. It has been proved that the density of keeping industrial chickens in cages of 1–3-Ɵer baƩeries provided by domesƟc norms should be extended to the baƩeries of new 12-Ɵer structures